1980
DOI: 10.1016/s0010-9452(80)80022-0
|View full text |Cite
|
Sign up to set email alerts
|

High Speed Memory Scanning in Parkinsonism

Abstract: This study tested the hypothesis that the slowing seen in parkinsonism includes cognitive as well as motoric components. The sample consisted of 20 nondemented parkinsonian patients, group matched to 16 normals by age, education, and verbal IQ. Each group was divided into young (64 and under) and old (65 and over) subsets. The Sternberg character classification paradigm was used to measure the speed and accuracy of one cognitive function, short term memory scanning. Following a logarithmic transformation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
1
2

Year Published

1988
1988
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(55 citation statements)
references
References 5 publications
0
52
1
2
Order By: Relevance
“…These impairments include slowed scanning on a visual recognition task (26) and slowing on motor response tasks that can reflect both bradykinesia and a central defect of motor programming (24). Mortimer et al (27) and Pirozzolo et al (28) observed that, among parkinsonism patients, bradykinesia correlated significantly with poorer performances on tests involving psychomotor speed, visual-spatial performances, and memory for spatial orientation.…”
Section: Discussionmentioning
confidence: 99%
“…These impairments include slowed scanning on a visual recognition task (26) and slowing on motor response tasks that can reflect both bradykinesia and a central defect of motor programming (24). Mortimer et al (27) and Pirozzolo et al (28) observed that, among parkinsonism patients, bradykinesia correlated significantly with poorer performances on tests involving psychomotor speed, visual-spatial performances, and memory for spatial orientation.…”
Section: Discussionmentioning
confidence: 99%
“…The most consistent findings in patients with PD are deficits of working memory (Owen, 1993;Cooper, 1993Cooper, , 1992Bradley, 1989;Wilson, 1980) and explicit memory (Buytenhuijs, 1994;Taylor, 1990Taylor, , 1986. Working memory can be defined as the ability to hold internal representations in short-term memory and to manipulate this mnemonic information on line to enable adaptive behaviour to be based on these representations rather than on immediate stimuli (Goldman-Rakic, 1987).…”
Section: Cognitive Deficits In Non-demented Pd Patientsmentioning
confidence: 94%
“…Mounting evidence indicates that PD, apart from the typical motor signs (Lang & Lozano, 1998;Gibb & Lees, 1988), is often accompanied by a variety of cognitive deficits (Caballol, Marti, & Tolosa, 2007;Pirozzolo, Hansch, Mortimer, Webster, & Kuskowski, 1982;Reitan & Boll, 1971), including rather subtle difficulties in visual-spatial perception (Boller et al, 1984), memory (Flowers & Robertson, 1985;Wilson, Kaszniak, Klawans, & Garron, 1980), language (Matison, Mayeux, Rosen, & Fahn, 1982), concept formation, and behavioral regulation (Flowers & Robertson, 1985;Cools, van den Bercken, Horstink, van Spaendonck, & Berger, 1984;Lees & Smith, 1983;Bowen, Kamienny, Burns, & Yahr, 1975), which suggests the involvement of the BG and the cortico-subcortical loops of which they are part in the regulation of these cognitive functions.…”
Section: Introductionmentioning
confidence: 99%